Reflections on an International Research Immersion Field Study as a High Impact Practice to Produce Publishable Papers by Underrepresented Undergraduates - Hill, Heather M.; Karlin, Melissa (Frontiers in Psychology, 2019)
Engaging undergraduates in publishable research is challenging. Skills including researching topics, statistical knowledge, and writing abilities are necessary; however, students often face time constraints or financial challenges that impede them from engaging in these experiences. Conducting research with underrepresented students can be an even bigger challenge, as these groups are known to face additional financial or family burdens that the traditional student does not face. This essay reports on the development of an international field study with the goal of producing publishable research by undergraduates. To date, 27 students (68% Hispanic, 52% first generation) have participated in a week-long immersion field experience in Roatán, Honduras. As an interdisciplinary field study, students were exposed to animal behavior, ecology concepts, and research methods through a two-course sequence that incorporated the field experience. In this essay, we share our best practices for conducting a field study with students from underrepresented populations with the goal of producing publishable research. We include the evolution of the course curriculum that was informed by self-reported student experiences and a brief description of some of the projects students designed. Students reported that the field experience highlighted the importance of adjusting research plans and expectations. Ultimately, this program exposed students to advantages and disadvantages of conducting field research while increasing confidence in their ability to conduct effective and meaningful research. A minimum of two semesters may be needed to create publishable research projects and one week of data collection is not sufficient for successful research projects.